2014
DOI: 10.5093/tr2014a5
|View full text |Cite
|
Sign up to set email alerts
|

Organizational citizenship behavior, organizational justice, job stress, and workfamily conflict: Examination of their interrelationships with respondents from a non-Western culture

Abstract: This study proposed two plausible models regarding these interrelationships: 1) The first model posited a positive relationship between (i) organizational justice and OCB, (ii) stress and OCB, and (iii) work-family conflict and stress. This first model indicates that the variables OCB and stress mediate between organizational justice and work-family conflict. 2) The second model proposes a positive relationship between (i) organizational justice and OCB, (ii) work-family conflict and OCB, and (iii) work-family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 43 publications
5
75
1
9
Order By: Relevance
“…The result of the relation of WLC and OCB in present study, confirmed the notion of Dorio et al (2008), Amstad (2011), andTziner andSharoni (2014) who also found the significant negative effect of WLC (work-life interference) and OCB. On the contrary, the present study does not support the result previous research from Lambert (2000), Baral and Bhargava (2010), Kasraie et al (2014), and Pradhan et al (2016) who all found the significant positive relations.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The result of the relation of WLC and OCB in present study, confirmed the notion of Dorio et al (2008), Amstad (2011), andTziner andSharoni (2014) who also found the significant negative effect of WLC (work-life interference) and OCB. On the contrary, the present study does not support the result previous research from Lambert (2000), Baral and Bhargava (2010), Kasraie et al (2014), and Pradhan et al (2016) who all found the significant positive relations.…”
Section: Resultssupporting
confidence: 80%
“…Dorio et al (2008) indicated that there is a negative relationship between WLC and OCB. Result from Amstad et al (2011) and Tziner & Sharoni (2014) found that work-family conflict was negatively related (-.39) with OCB. Meanwhile, Carlson et al (2013) using participants from western culture discussed the relationship between WLC, WLB and OCB.…”
Section: H 2b : Wlb Have a Significant Positive Effect On Organizatiomentioning
confidence: 99%
“…In other words, the WFC refers to situations in which job requirements generate employees certain conflicts with the family or vice versa (Jiang, 2012). Greenhaus and Beutell (1985) identify three types: (a) conflict based on time, where the time demanded in one life domain decreases availability in the other, reducing energy and creating stress; (b) conflict based on tension, where the stress experienced in one role affects the performance in the other; and (c) conflict based on behavior, which consists of the incompatibility between various and desired behaviors in the two competing domains (Tziner and Sharoni, 2014).…”
Section: Interactional Justicementioning
confidence: 99%
“…When employees perceive an excessive workload over their capabilities it can be defined as job stress (Tziner & Sharoni, 2014). Job stress was found to have a positively significant influence on compulsory citizenship behaviour (Zhan et al, 2017).…”
Section: Job Stressmentioning
confidence: 99%